الاستيطان الفينيقي في جزر البحر المتوسط وساحل شبه جزيرة أيبيريا: من خلال المصادر الأثرية والأدبية (Journal of Academic Research, 2024)
Phoenician settlements spread on many islands in the Mediterranean, and the island of Cyprus is one of the first islands in the Mediterranean that witnessed an early Phoenician presence. The books of the Old Testament indicated the existence of a relationship between Cyprus and the coast of Phenicia, and linguistic studies also confirmed the existence of aspects of influence and influence with Carthage. Also the island of Malta has an important strategic location in the middle of the Mediterranean, and it is one of the islands that witnessed Phoenician settlement, like other islands throughout the Mediterranean. Many classical writings have referred to that settlement and it has been confirmed through a number of inscriptions. As for Sicily, the classical sources indicated the importance of the strategic location, and that this helped in settling the Phoenicians on all its shores, and the results of archaeological excavations. In the Balearic Islands, archaeological evidence indicates that the island was one of the centers of Phoenician industry in the western Mediterranean, and in Sardinia, the history of the Phoenician presence dates back, according to some historical accounts, to around the end of the second millennium BC. Archaeological studies conducted on the island have proven that Phoenician settlements there It was concentrated in the southern corner, where its most important city was Nora. In the Iberian Peninsula, many natural resources were available, especially minerals, which was one of the most important reasons that prompted the Phoenicians to pass the Pillars of Hercules and reach them, where they settled in many places.